Improved method for synthesis of cysteine modified hyaluronic acid for in situ hydrogel formation1. Issue 47 (14th June 2015) - Zhang, Xin; Sun, Pengcheng; Huangshan, Lingzi; Hu, Bi-Huang; Messersmith, Phillip B.
<x xml:space="preserve">Abstract</x> We developed a new strategy for the functionalization of hyaluronic acid by chemical modification of its C-6 hydroxyl groups through an ether bond to obtain a cysteine–hyaluronic acid conjugate.